The Effect Of Using The Index Card Match Learning Model On Student Learning Outcome In Mathematic Subject In Elementary School - Ratnasari, Khurin; Akmad Zaeni; Sholihah, Mar’atus; Dasuki, Mohammad; Nurhidayati, Titin (International Conference on Humanity Education and Society (ICHES), 2024)
An active learning model that can be used in the classroom is the Index Card Match learning model. This learning model directs students to work together in completing tasks correctly with their friends. the use of this Index Card Match learning model can help students to make it easier to understand the material so that it can improve student learning outcomes. The main problem formulations in this study are: (1) Is there an effect of the use of the Index Card Match Learning Model on Student Learning Outcomes in Mathematics Subjects of Spatial Buildings Material at Cakru 01 State Elementary School: (1) Is there an effect of the use of the Index Card Match Learning Model on student cognitive learning outcomes (2) Is there an effect of the use of the Index Card Match Learning Model on student affective learning outcomes in mathematics subjects in the material of building space at Cakru 01 State Elementary School. The general objectives of this study are: (1) To determine the effect of the use of the Index Card Match learning model on student learning outcomes in mathematics subjects in the material of building space at SD Negeri Cakru 01. While the specific objectives of this study are: (1) To determine the effect of using the Index Card Match Learning Model on student cognitive learning outcomes. (2) To determine the effect of the use of the Index Card Match Learning Model on the affective learning outcomes of students in mathematics subjects in the material of building spaces at Cakru 01 State Elementary School. This research uses quantitative methods. The primary data source of this research is a questionnaire. While the secondary data sources are observation, interviews, and documentation. The data analysis techniques used are Normality Test and Paired Sample T-Test Test. This study successfully concluded that (1) There is an effect of the use of the Index Card Match Learning Model on student learning outcomes in mathematics subjects in the material of building space at Cakru 01 State Elementary School with a sig value. (2-tailed) 0.000 <0.05. (2) There is an Effect of Using the Index Card Match Learning Model on Student Cognitive Learning Outcomes with a sig value (2-tailed) 0.000 <0.05. (3) There is an effect of the use of the Index Card Match learning model on the affective learning outcomes of students in the mathematics subject of space building material at Cakru 01 State Elementary School with a sig (2-tailed) value of 0.000 <0.05.